Optimum Analytical Model for the Drift Region of Silicon Carbide Uni-polar Power Device - JIANG Huaping; LI Chengzhan; WU Yudong (Kongzhi Yu Xinxi Jishu)
Currently，doping concentration uniformity of epi-wafers is poor and thickness of epi-layer is sensitive to cost and defect density. An optimum analytical model for the drift region of uni-polar silicon carbide (SiC) power device and an optimum control line were developed based on the optimum target of specific resistance. The model was verified by simulation using Synopsys/Sentaurus. With consideration of the typical variations of thickness and doping concentration of epi-layer, parameters of optimum drift region were calculated for different voltage classes, which result in a 1~1.2 μm increase for every 100 V blocking voltage.